Midterm Outcomes of the Nellix Endovascular Aneurysm Sealing System: A Dual-Center Experience. (October 2016) - Silingardi, Roberto; Coppi, Giovanni; Ferrero, Emanuele; Lauricella, Antonio; Psacharopulo, Daniele; Saitta, Giuseppe; Viazzo, Andrea; Ferri, Michelangelo
Purpose: To report midterm outcomes of the Nellix Endovascular Aneurysm Sealing (EVAS) System in the treatment of abdominal aortic aneurysm (AAA).Methods: Between September 2013 and July 2014, 64 AAA patients (mean age 76.6±6.8 years; 61 men) were treated with the EVAS system at 2 centers (only procedures performed at least 12 months prior to the analysis were included). Most patients were treated for a stable AAA, while 1 patient was treated for a ruptured aneurysm. Mean aneurysm diameter was 57.3±9.3 mm. The proximal neck measured a mean 21.5±3.3 mm in diameter and 27.0±12.1 mm long; the neck angle was 16.9°±19.3°. Eleven (17.2%) patients were treated outside the instructions for use (IFU).Results: Technical success was achieved in 63 (98.4%) of 64 patients; 1 type Ia endoleak was treated intraoperatively. One (1.6%) aneurysm-related death occurred at 4 months due to a secondary aortoenteric fistula. Overall, endoleaks occurred in 3 (4.7%) patients (2 type Ia, 1 type II). The estimated rates for 18-month overall survival, freedom from aneurysm-related death, and freedom from secondary interventions were 92.7%, 98.4%, and 95.0%, respectively. Patients treated outside the IFU had a significantly higher incidence of device-related complications (p=0.03).Conclusion: The use of the Nellix device in everyday clinical practice is safe and offers promising midterm results. The risk of secondary aortoenteric fistula requires further analysis. Longer follow-up is needed to assess the actual efficacy of the device, although the risk of migration with late endoleak seems low.